Three new species of the Neurigona orbicularis species group from Brazil (Diptera: Dolichopodidae) - Da Silva, Paulo Cesar; Capellari, Renato S.; Oliveira, Sarah S. (Zootaxa, 2022)
The Neurigona orbicularis species group (Diptera: Dolichopodidae) is recorded from Brazil for the first time, and three new species are described and illustrated, including figures of the male genitalia: N. lopesi sp. nov. (Tocantins and Goiás, Cerrado biome), N. papaveroi sp. nov. (Mato Grosso, Cerrado biome) and N. tingua sp. nov. (Rio de Janeiro, Atlantic Forest biome). Additionally, N. orbicularis Becker, previously known only from the type-locality in Paraguay, is newly recorded from the Brazilian States of Mato Grosso do Sul (Pantanal biome) and São Paulo (Atlantic Forest biome) and its hypopygium is also illustrated. An updated identification key to males of the orbicularis-group is provided.